The Effect Of Financial Technology Use And Financial Literacy On Financial Management Among Management Students At Unpab - Novania Trifana; Ramadhan Harahap; Pipit Buana Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the role of financial technology use and financial literacy levels in shaping the financial management of students in the Management Study Program of the 2022 Panca Budi Development University, Medan. The study used a quantitative approach by collecting data from 80 randomly selected respondents. Data were obtained through questionnaires and analyzed using multiple linear regression. The analysis results showed that financial technology use did not have a significant impact on student financial management, as reflected by a significance value of 0.118. Conversely, financial literacy was shown to have a significant impact on financial management with a significance value of 0.000. Simultaneous testing showed that financial technology and financial literacy jointly contributed to student financial management with a coefficient of determination of 0.443, meaning that 44.3 percent of the variation in financial management can be explained by these two variables. This finding confirms that the ability to understand and manage finances plays a more dominant role than technological convenience in shaping students' financial management behavior.